Penyebab Terjadinya Ruptur Perineum pada Persalinan Normal di RSUD Muntilan Kabupaten Magelang - Eka Prawitasari; Anafrin Yugistyowati; Dyah Kartika Sari (Alma Ata University Press, 2015)
Perineal Rupture is a laceration on perineum when delivering a baby. Perineal rupture is one of lacerations on birth canal which can cause complication which is dangerous for mother. The danger and complication of perineal rupture are bleeding, hematoma, ﬁ stula, and infection. Based on the baseline study in RSUD Muntilan Magelang District, the number of normal deliveries in November 2013 to June 2014 found 612 people with normal delivery (spontaneous), as many as 243 people with a rupture perineum and the majority occur in women primiparous total of 37 people (15.22%), at a birth spacing >2 years as many as 87 people (35.80%), maternal aged 20-35 years as many as 46 people (18.93%), and 2.500-4.000 grams birth weight as much as 73 people (30.04%). The purposes of this study were to know the frequency distribution of perineal rupture on normal delivery and to know the relationship between perineal rupture and partum, birth spacing, mothers’ age, birth weight on normal delivery in RSUD Muntilan Magelang District of 2015. This study was observational analytics with cross sectional design. The research samples were 41 women of spontaneous vaginal delivery in RSUD Muntilan. The data were collected by using checklist. Based on the statistical test, there were no signiﬁ cant relationship between perineal rupture and partum (p-value=0.893), birth spacing (p-value=0.682), and mothers age (p-value=0.434); while on birth weight there was a signiﬁ cant relationship with the occurrence of rupture perineum (p-value=0.000). In conclusion, there was no inﬂ uence between partum, birth spacing, and mothers’ age on perineal rupture. In this study, the factor that inﬂ uences perineal rupture was the birth weight.